2015
DOI: 10.1017/s0020818314000411
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Terrorism: Leadership Deficits and Militant Group Tactics

Abstract: Certain types of militant groups—those suffering from leadership deficits—are more likely to attack civilians. Their leadership deficits exacerbate the principal-agent problem between leaders and foot soldiers, who have stronger incentives to harm civilians. We establish the validity of this proposition with a tripartite research strategy that balances generalizability and identification. First, we demonstrate in a sample of militant organizations operating in the Middle East and North Africa that those lackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 102 publications
2
56
1
2
Order By: Relevance
“…However, even though leaders were more ideologically committed to the group's goals and ideologies, with regard to our primary variable of interest, use of violence, we found that they were at the same time less likely to engage in violent acts. These results obtained on the individual level support prior research on groups and organizations (Abrahms & Potter, 2015;Shapiro & Siegel, 2012) suggesting that leaders, in comparison to followers, have fewer incentives to perpetrate violence. As we argued above, several variables may motivate followers to engage in violent actions.…”
Section: Leaders Followers and Violence In Extremist Groups 19supporting
confidence: 83%
See 1 more Smart Citation
“…However, even though leaders were more ideologically committed to the group's goals and ideologies, with regard to our primary variable of interest, use of violence, we found that they were at the same time less likely to engage in violent acts. These results obtained on the individual level support prior research on groups and organizations (Abrahms & Potter, 2015;Shapiro & Siegel, 2012) suggesting that leaders, in comparison to followers, have fewer incentives to perpetrate violence. As we argued above, several variables may motivate followers to engage in violent actions.…”
Section: Leaders Followers and Violence In Extremist Groups 19supporting
confidence: 83%
“…There are several reasons to expect that the incentives of leaders to engage in violent actions are indeed weaker than the incentives of followers for such actions (Abrahms & Potter, 2015;Shapiro & Siegel, 2012). First, due to their position within the group, compared to followers, leaders have a more complete understanding of long-term organizational goals and better recognition of appropriate means for attaining them (Greenwald, 2007;Von Krogh et al, 2012).…”
Section: Group Role and Propensity To Use Violencementioning
confidence: 99%
“…We use rebel centralized leadership to account for the rebel groups' type of command structure and the possible influence of principal-agent problems (Abrahms and Potter 2015). We distinguish between groups with a strong centralized leadership and those that are internally factionalized (Cunningham, Gleditsch and Salehyan 2009).…”
Section: Data and Research Designmentioning
confidence: 99%
“…We identified five sub-brakes under Brake 5. It is likely that the effectiveness of Brakes 5a -5d will be associated with the effectiveness of organisational leadership, with these brakes being least effective in organisations experiencing 'leadership deficits' (Abrahms & Potter, 2015), or that explicitly adopt strategies of leaderless resistance (Chermak et al, 2013).…”
Section: Brake 4a Resistance To Generalisations About Their Opponentsmentioning
confidence: 99%